Imaging in major salivary gland diseases - C. Botsios; P. Sfriso; C. Grava; P. Ostuni; M. Andretta; A. Tregnaghi; P. Zucchetta; PF. Gambari (PAGEPress Publications, 2001)
Most of the salivary glands diseases are characterized only by a few distinct clinical patterns. Medical history and clinical examination are still considered of great relevance. However, in order to obtaine a definite diagnosis, imaging techniques are required in most of the cases. Salivary glands ultrasonography (US) is the technique to be used as the first because US can easily differentiate calculosis, inflammatory diseases and tumors. Sonography is also frequently needed to perform needle aspiration or biopsy (FNAC). Sialography should be used essentially for assessing chronic sialoadenitis as well as Sjögren's syndrome. At present, Magnetic Resonance sialography should be preferred because of the greater sensibility in diagnosing inflammatory diseases of the salivary glands. It allows to evaluate both intraglandular oedema and nodules, so that incannulation of the salivary duct is not required. Computer Tomography (CT) and Magnetic Resonance imaging (MR) are useful when neoplasm are suspected, particularly if deep areas of the gland, which cannot be visualized by US, are involved. Sequential scintigraphy is currently employed for assessing the functional status of all the 4 major salivary glands and evaluating the chronic evolution of glandular damage.